The implementation of a blended education system at the Foreign Language Department of the University of El Salvador, for students in 4th and 5th year of Licenciatura en Lenguas Modernas, Especialidad en Francés e Inglés and, Licenciatura en Idioma Inglés Opción Enseñanza - Acosta Aguilar, Marlene Isabel
The following work aims to understand the importance of the implementation of Blended Learning at Foreign Language Department at University of El Salvador, in order to help students of 4th and 5th year of the Licenciatura en Lenguas Modernas, Especialidad en Francés e Inglés and of the Licenciatura en Idioma Inglés, Opción Enseñanza that struggle with schedule issues or living in remote areas among others.